2003
DOI: 10.1111/j.1728-4465.2003.00008.x
|View full text |Cite
|
Sign up to set email alerts
|

Gender‐role Attitudes among Egyptian Adolescents

Abstract: Using nationally representative survey data, this study explores gender‐role attitudes among unmarried adolescents aged 16–19 in Egypt, a society characterized by distinct and often segregated roles for men and women. Adolescents' views about desirable qualities in a spouse as well as more direct indicators of gender‐role attitudes are examined, including opinions about whether wives should defer to their husbands, share in household decision making, and have the responsibility for performing domestic tasks. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
72
2
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(84 citation statements)
references
References 13 publications
7
72
2
3
Order By: Relevance
“…Gender attitudes of youth can potentially contribute to our understanding of root causes of violence against women. The overall findings that boys report significantly higher levels of patriarchal gender attitudes compared to girls is similar to those from other studies conducted in Egypt [15], USA [16], and Brazil [17]. …”
Section: Discussionsupporting
confidence: 88%
“…Gender attitudes of youth can potentially contribute to our understanding of root causes of violence against women. The overall findings that boys report significantly higher levels of patriarchal gender attitudes compared to girls is similar to those from other studies conducted in Egypt [15], USA [16], and Brazil [17]. …”
Section: Discussionsupporting
confidence: 88%
“…One finding that is recurrent in western and non-western countries is that male respondents are generally more traditional minded than their female counterparts (Burt & Scott, 2002;Carlson & Knoester, 2011;Crouter et al, 2007;Davis & Wills, 2010;Fan & Marini, 2000;Kucinskas, 2010;Kulik, 2000a;Marks, Bun, & McHale, 2009;Mensch et al, 2003;Nelson & Keith, 1990;Richmond-Abbott, 1984;Sagara & Kang, 1998;Stephan & Corder, 1985;Streitmatter, SantaCruz, & Ellis-Schwabe, 1984). Three longitudinal U.S. studies conclude that the difference between boys and girls narrows over time (Davis, 2007;Fan & Marini, 2000;Tallichet & Willits, 1986), although this is contested by another U.S. study of Galambos, Almeida, and Petersen (1990), who found boys becoming less egalitarian and girls more egalitarian over time.…”
Section: Table 3 (Continued)mentioning
confidence: 99%
“…First, most studies found a positive relationship between the offspring's egalitarian views and both mothers' education (Antill et al, 2003;Davis, 2007;Ex & Janssens, 1998;Fan & Marini, 2000;Kiecolt & Acock, 1988;Kulik, 2002a;Marks et al, 2009;Richmond-Abbott, 1984;Tallichet & Willits, 1986) and fathers' education (Antill et al, 2003;Fan & Marini, 2000;Kulik, 2002a;Marks et al, 2009;Mensch et al, 2003;Richmond-Abbott, 1984;Thornton et al, 1983): Parents with higher educational levels have more egalitarian offspring. Ex and Janssens (1998) stated that the influence of maternal education on her child's GRA acts through its influence on other variables such as parental GRA and employment.…”
Section: Parents' Socioeconomic Status (Ses)mentioning
confidence: 99%
“…Meanwhile, the gender dichotomy is aimed at controlling female behaviour. Women and young people were subordinated in their respective social spaces to the ruling adult male condition (Fitouri 1994;Mensch 2003). The hegemonic impositions together with economic and political instability, have limited the possibilities of social and cultural change with regard to values and social behaviour as well as to the types of social relationships among young people 'allowed' by 'adults'.…”
Section: Life Cycle Cultural Images and Social Markersmentioning
confidence: 99%